Sleep quality according to academic progression in Chilean Obstetrics students - Fanny López Alegría; Juan Carlos Oyanedel Sepúlveda; Gonzalo Rivera-López (Medisur)
Foundation: sleep is recognized as an indicator of quality of life and, in a student´s daily life, it acquires great importance for its relationship with cognitive functioning and academic activities. Objective: to identify and evaluate factors associated with quality of sleep presented by the Chilean students of the Obstetric training program, according to years studied. Methods: cross-sectional and analytical study conducted in the 2018 school year in a Chilean university, which included all the students of Obstetrics, who answered a questionnaire that evaluated sociodemographic background, academic profile, previous sleep habits and sleep quality, assessed by the Pittsburgh Sleep Quality Index (PSQI) survey. Results: the behavior around the sleep habits differs significantly among courses, in the 1st and 4th year there are those who sleep less and the students of this last course are classified as the worst sleepers. The average of the PSQI components varies between 6, 6 (5th year) and 9.2 (4th year); daytime dysfunction component showed the most extreme values. Conclusions: there is a weak association between sleeping quality and sociodemographic variables, academic profile and previous sleep habits. It is only strongly associated with some components of the sleep quality survey, such as bedtime and student sleeping hours. The training program progression does not mean an increase or decrease in bad or good sleepers.